ANTIBAKTERI KUMPAI MAHUNG (Einulifolium H.B&K) TERHADAP Salmonella Typhi - Dwi Rizki Febrianti; Rakhmadhan Niah; Novia Ariani (Jurnal Insan Farmasi Indonesia, 2020)
Kumpai mahung is an endemic plant of South Kalimantan which grows in the plains of Meratus mountains. Previous research stated that this plant has potential as an anti-inflammatory against mice and has good antioxidant content. This study aims to determine the activity of kumpai mahung extract against salmonella typhi bacteria. The results of previous studies stated that the phytochemical screening of kumpai mahung extract positively contained flavonoids, alkaloids, tannins and saponins which had the potential to have antibacterial activity. Using the well method with a concentration series of 100%, 75% and 50% and calculated the inhibition zone formed with callipers. The results showed that the mean inhibition zone formed was 19.8 ± 0.2 mm (100%), 17.07 ± 0.1 mm (75%) and 13.9 ± 0.1 mm (50%). It can be concluded that all concentrations have a strong potential against salmonella typhi bacteria.